Ethnobotanical Study of Fig Tree (Ficus Carica L.) And Olive (Olea Europaea L.) From Tetouan Province In Morocco And Study Their Antimicrobial Activity - Mennane Zakaria; Tabet Zahira; El kharraz Btissam; Aabid Touria; Souhaila Touil; Emrani Adnan; Abrini Jamal; Elmtili Noureddine (E3S Web of Conferences, 2021)
This study we have conducted an ethnobotanical survey and antimicrobial activity in Tetouan province to identify the use of the famous plant species in traditional medicine : fig tree and Olive and follow-up of antimicrobial activity during three stages for green, pink and black olives and mixing activity of olive and fig extracts. 80 questionnaire sheets were done during April-June 2019, and the method of diffusion was used for the antimicrobial activity.Bacteria and yeasts were used: Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae, E.coli and Candida albicans. The results revealed that 32% of farmers use olive oil for the initial treatment of respiratory diseases, and 22% use it for digestive system problems and 13% use it as a treatment of the nervous system.However, fig tree is used against insect bites, as an inhibitor of the growth of certain cancerous tumors, diabetes and certain viral infections. The ethanol extracts showed good inhibitory effects against most strains of bacteria and yeast. Also for the majority of strains tested, it was found that in December (black olive), activity is stronger, and that the mixture of ethanol extracts with ethanol extracts of fig tree it strengthened them.